Xenon arc photocoagulation for treatment of subluxation of lens. Issue 4 (April 1985) - Lamba, P. A.; Kumar, D. S.; Arora, A.
Abstract : In the treatment of congenital or acquired subluxation of the lens a conservative approach to reposition the pupil in front of the aphakic area by the use of the xenon arc photocoagulator is emphasised. The management of two cases of subluxation is discussed in detail and the results evaluated. The ease of repositioning the pupil by means of iris photocoagulation and the absence of surgical complications are indications for the use of this non-invasive procedure in the treatment of subluxated lenses.